Kur’ an- ı Kerim’ de Hz. Peygamber’ e (S.A.V.) yapılan teselliler - Aldemir, Halil (My University, 2001)
Kur'ân-ı Kerîm'de Hz. Peygamber'e (s.a.v.) Yapılan Tesellîler adını verdiğimiz tezimiz, üç bölümden oluşmaktadır. Birinci bölümde peygamberlik, peygamberler, peygamberlerin gönderiliş gayesi, davetleri, insanların onlara karşı gösterdikleri tavırlar ile Hz. Muhammed'in (s.a.v.) peygamberliği üzerinde durduk. İnsanlar Hz. Peygamber'in (s.a.v.) peygamberliğine ve onun getirdiği vahye bazı nedenlerden dolayı iman etmiyorlardı. Onların söz konusu karşı çıkmaları, peygamberliği ve peygamberleri tanımamalarından ileri gelmekteydi. Bundan dolayıdır ki, bu bölümde bu konulara yer verdik. İkinci bölümde ise Hz. Peygamber'in (s.a.v.) vahiy sürecinde çektiği sıkıntılara ve bu sıkıntıların şiddetine yer verdik. Ancak müşriklerin Hz. Peygamber'i (s.a.v.) ve ashabını üzen tekzip, alay, inkar ve hatta işkence gibi tavırlarından sadece Kur'an'da geçen ya da bariz bir şekilde işaret edilenleri açıklamaya dikkat ettik. Çünkü meselenin hadislerde ve siyer kitaplarında kalan kısmı ise konumuzun sınırlarını aşmaktadır. Yine de yeri geldikçe hadislere ve diğer rivayetlere değindik. Böylece onun ne derece tesellîye ihtiyaç duyduğunu açıklamaya çalıştık. Üçüncü ve son bölümde ise tesellînin anlamını, Kur'an'da yapılan tesellîleri, Kur'an ilimleri ile tesellî arasında kurulan bağları ve Hz. Peygamber'e (s.a.v.) yönelik tesellîleri inceledik. Gerçekten de tesellî sınırları geniş olan bir konudur. Müfessirler bir çok ayeti bu konuyla irtibatlandırarak izah etmişlerdir. Bundan dolayı bu bölümde tesellînin ne kadar geniş bir konu olduğunu ve müfessirlerden ne derece ilgi gördüğünü göstermek için Hz. Peygamber (s.a.v.) dışındaki insanlara yapılan tesellîleri kısaca belirtikten sonra son peygamber Hz. Muhammed'e (s.a.v.) yapılan tesellî şekillerine yer vererek tezimizi noktaladık.

Our study which we called as consolatins made to Hz. Prophet in the Qur'an, consists of three sections. In the first section, we focused on the prophethood, prophets, the aim of sending prophets,their messages, the human beings' attitudes towards them and prophethood of Hz. Muhammad. Human beings has not believed in the prophethood of Hz. Prophet and the message with which He has been send because of some reasons. Such their objections resulted from the being unaware of the prophethood and prophets. For this reasons we studied on these subjects in this section. In the second section, we analysed the annoyances which Hz. Prophet experienced in the process of sending out messages and the severity of these annoyances. However we were very careful about the explaining only explicitly marked annoyances and mentioned annoyances in the Qur'an from the attitutes of disbelievers as denial, objections, mockery and even tortures which hurt the feelings of Hz. Prophets and his followers. Because the rest of the subjects which mentioned in hadiths and history books is out of contents of our study. Nevertheless, we mentioned the hadiths and the other narrations when they are needed. So we tried to explain what degree consolatins are needed by him. In the third and last section we searched for the meaning of consolation, the consolations in the Qur'an, the relationships established between the sciences of Qur'an and consolation and consolations towards Hz. Prophet. Indeed the consolation is the subject including very extensive borders. Interpretators have explained lots of ayats by refering to this topic. Because of this, in this section we finished our study with explaining the sorts of consolation which Hz. Muhammed faced after the pointing out the consolation which the other persons faced in order to show what the consolatin is extensive topic and the importance which the interpretators give it.
Keywords: Din; HZ. MUHAMMED (S.A.V.); İslam Dini; KUR’AN-I KERİM; Tefsir ve tefsir ilmi